2016
DOI: 10.1073/pnas.1605733113
|View full text |Cite
|
Sign up to set email alerts
|

Physical coupling of activation and derepression activities to maintain an active transcriptional state at FLC

Abstract: Establishment and maintenance of gene expression states is central to development and differentiation. Transcriptional and epigenetic mechanisms interconnect in poorly understood ways to determine these states. We explore these mechanisms through dissection of the regulation of Arabidopsis thaliana FLOWERING LOCUS C (FLC). FLC can be present in a transcriptionally active state marked by H3K36me3 or a silent state marked by H3K27me3. Here, we investigate the trans factors modifying these opposing histone states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 53 publications
(110 reference statements)
3
49
0
3
Order By: Relevance
“…This together with the enrichment in H3K36me3 toward the 3end of genes spearheaded the link between H3K36 methylation and transcription elongation in animals and yeast (Wang et al, 2009). In Arabidopsis, we and others (Yang et al, 2016;Zhong et al, 2019) demonstrate that SDG8, like its orthologs, can bind RNAPII. However, while SDG8 orthologs preferentially bind the phosphorylated CTD of elongating RNAPII, we found that SDG8 can interact with both the inactive (non-phosphorylated) and active (Ser5P and/or Ser2P) forms of RNAPII (Figure 6).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This together with the enrichment in H3K36me3 toward the 3end of genes spearheaded the link between H3K36 methylation and transcription elongation in animals and yeast (Wang et al, 2009). In Arabidopsis, we and others (Yang et al, 2016;Zhong et al, 2019) demonstrate that SDG8, like its orthologs, can bind RNAPII. However, while SDG8 orthologs preferentially bind the phosphorylated CTD of elongating RNAPII, we found that SDG8 can interact with both the inactive (non-phosphorylated) and active (Ser5P and/or Ser2P) forms of RNAPII (Figure 6).…”
Section: Discussionsupporting
confidence: 53%
“…DNA was purified with the NucleoSpin Gel and PCR Clean-up kit (Macherey−Nagel, DĂŒren, Germany) and analyzed by real-time PCR (LightCycler 480II; Roche in conjunction with the SYBR Green Master mix) using gene-specific primers listed in Supplementary Table S1. Data were analyzed as described in Zhao et al, 2019 for H3K4me3 andH3K36me3 andin Yang et al, 2016 for RNAPII. A mock control was done using uncoupled magnetic beads (Supplementary Figure S5).…”
Section: Western Blotting and Chromatin Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because SDG8 does not possess the G-box, TGGGCC/T and TAATTA binding domain, it is tempting to speculate that it may act in a combination with other transcription factors that are able to bind G-box and/or FORC A motifs directly to regulate downstream genes. Finally, other processes may enable SDG8 recruitment, especially when considering its interaction with the RNA PolII, the zinc finger domain-containing H3K27 demethylase ELF6 or even H3K4me1 through its CW domain (Hoppmann et al, 2011;Yang et al, 2016;Liu & Huang, 2018).…”
Section: Researchmentioning
confidence: 99%
“…SDG8 is the major H3K36me3 methyltransferase in Arabidopsis ( Yang et al, 2014 ) and is required for H3K36me3 deposition at the FLC locus ( Shafiq et al, 2014 ; Yang et al, 2014 ). SDG8 associates with components of the transcription machinery, including RNA Pol II and PAF1, as well as with the H3K27 demethylase EARLY FLOWERING 6 (ELF6) ( Yang et al, 2016 ). These physical associations ( Figure 2 ) couple removal of repressive histone marks with deposition of active marks and transcription initiation/elongation to sustain high levels of FLC expression.…”
Section: Roles Of Trxg Factors In Floral Induction At the Shoot Apicamentioning
confidence: 99%